The effect of graphic organizer on student's learning in school. - Zaini, Syaza Hazwani; Mokhtar, Siti Zalina; Nawawi, Mokhtar (Malaysian Educational Technology Association (META), 2010)
Graphic organizers are instrument of representation , illustration and modelling of information in visuals or graphics form that use to achieve a meaningful learning. GOs are a set of learning strategies which involve translating words expressed in linear form into visual structures. When written material or difficult concepts are expressed graphically, the students can develop alternative structures for understanding the course concepts. In this paper, illustrate the use of graphic organizers on the effects of students’ l earning in schools. Previous research studies investigating on the effects of graphic organizers on students' learning in schools are reviewed. It was found that graphic organizers had effect on the improvement of students’ comprehension, performance and motivation in learning.